SO SÁNH SỰ XUẤT HIỆN CỦA SPREAD F XÍCH ĐẠO TỪ TRONG NĂM MẶT TRỜI HOẠT ĐỘNG TRUNG BÌNH (2003) VÀ HOẠT ĐỘNG YẾU (2005) - Lan, Hoàng Thái; Trang, Nguyễn Thu; MACDOUGALL, JOHN (Vietnam Journal of Earth Sciences, 2011)
The occurrence of equatorial spread F over Ho Chi Minh City in years 2003 and 2005 This paper presents results of the study of spread F based on the ionograms obtained at Ho Chi Minh City (Vietnam) for year 2003 (medium solar activity) and year 2005 (weak solar activity) under quiet geomagnetic conditions. The characteristics of Spread F over Vietnam showed a tendency with a decrease and later occurrence in the year of weaker solar activity. The seasonal variations showed maximum in March - April and minimum in December. The Range Spread F (Fs_Q) that related to scintillations of radio signals between satellites and ground stations occurred pre-midnight and appeared more in February, March and April. The time of appearance of the Fs_Q in the year 2005 occurred later than in the year 2003. The Frequency Spread F (Fs_F) occurred post-midnight and showed maximum of occurrence during equinoxial months. These results were also compared with results of other equatorial stations.